Optimalisasi Pengaturan Layanan Urun Dana (Crowdfunding) Berbasis Teknologi Informasi Sebagai Solusi Permodalan Usaha Mikro, Kecil, Dan Menengah Di Masa Pandemi Covid-19 - Rafi Aulia Ibrahim; Chairul Yaqin; Marthin James Simbolon (Lex Renaissance, 2021)
This study aims to compare crowdfunding with other methods of capital, namely the capital market, banking credit, and P2P lending, as well as assess changes to the Financial Services Authority Regulation (POJK) regarding crowdfunding in the context of the realization of responsive and fair laws during the COVID-19 pandemic. In addition, this study also aims to analyze how information technology-based crowdfunding arrangements encourage the digitization of MSMEs. The research method used is normative juridical using secondary data sourced from literature studies of books, journals, articles, and statutory regulations. The results of the study conclude that, first, crowdfunding provides an alternative method of capitalization for MSMEs in terms of requirements and costs that are easier, as well as secondary market orientation and investors. Second, the latest POJK on crowdfunding shows changes that are more accommodating to MSMEs. However, the POJK can still be refined, especially in the context of the limited authority of the Indonesian Crowdfunding Service Association (ALUDI) in crowdfunding supervision. Making ALUDI a Self-Regulatory Organization (SRO) is one solution to this problem.Keywords: Crowdfunding; digitalization; financial technology; MSME; OJK RegulationAbstrakPenelitian ini bertujuan untuk membandingkan crowdfunding dengan metode permodalan lainnya, yakni pasar modal, kredit perbankan, dan P2P lending, serta menilai perubahan Peraturan Otoritas Jasa Keuangan (POJK) tentang crowdfunding dalam konteks perwujudan hukum yang responsif dan berkeadilan di masa pandemi COVID-19. Selain itu, penelitian ini juga bertujuan menganalisis bagaimana pengaturan crowdfunding berbasis teknologi informasi mendorong digitalisasi UMKM. Metode penelitian yang digunakan adalah yuridis normatif menggunakan data sekunder yang bersumber dari studi kepustakaan buku, jurnal, artikel, serta peraturan perundang-undangan. Hasil penelitian menyimpulkan bahwa, pertama,  crowdfunding menyediakan alternatif metode permodalan bagi UMKM dari segi persyaratan dan biaya yang lebih mudah, serta orientasi pasar sekunder dan pemodalnya. Kedua, POJK terbaru tentang crowdfunding menunjukkan perubahan yang lebih mengakomodasi UMKM. Namun, POJK tersebut masih dapat disempurnakan kembali, terutama dalam konteks keterbatasan kewenangan Asosiasi Layanan Urun Dana Indonesia (ALUDI) dalam pengawasan crowdfunding. Menjadikan ALUDI sebagai Self-Regulatory Organization (SRO) merupakan salah satu solusi dari masalah tersebut.Kata Kunci: Crowdfunding; digitalisasi; financial technology; POJK; UMKM